Synthesis and Dyeing Action of Novel Thioindigoid Reactive Dyes - Kumar Upadhyay, Raj; Attri, Seema; Upadhyay, Sanidhya; Kumar Tiwari, Hemandra (Asian Journal of Chemistry, 2011)
Some thioindigoid dyes synthesized by condensation of thiazolidinones with isatin are evaluated for their dyeing action in terms of dye exhaustion and fixation on cotton, polyester, silk and wool fibrics. Structures of products have been elucidated from molecular weight, elemental analysis, infrared and NMR spectroscopy.